Chronic fatigue syndrome – challenge in diagnosis and management: a literature review - Nieciecka, Adrianna; Tomys-Składowska, Julia; Lamch, Magdalena; Jabłońska, Monika; Błasik, Natalia; Janiszewska, Marta; Wójcik-Kula, Agata (Journal of Medical Science, 2023)
Introduction. Chronic fatigue syndrome is a disease that includes a number of various symptoms, among which the most characteristic symptom is fatigue. Diagnostic criteria are not unambiguous and vary depending on the scientific society by which they were developed. The aim of this review is to discuss the phenomenon of chronic fatigue, including its diagnostic criteria, epidemiology, pathophysiology, symptoms, and pharmacological and non-pharmacological strategies.Material and methods. 45 articles published were reviewed and placed in the PubMed and Google Scholar databases.Results. Chronic fatigue syndrome is defined as a group of symptoms whose dominant symptom is fatigue that persists after rest for at least 6 months. The Oxford or CDC criteria are most commonly used to make the diagnosis. Statistics on prevalence are inconclusive. There are several theories of origin - infectious, immunological, neuroendocrine, bioenergetic, neurological, autonomic and genetic. Other symptoms of chronic fatigue syndrome include sleep and memory disorders or muscle and joint pain. Current treatment focuses on symptomatic treatment, including education, diet, and physical activity, as well as pharmacotherapy for pain, sleep, and cognition.Discussion. Diagnosis and treatment of chronic fatigue syndrome undoubtedly is a medical challenge, due to non-specific symptoms, multifactorial pathogenesis and difficult to estimate prevalence of this disease. Future scientific development should focus especially on exploring the pathomechanism of CFS, which would enable the implementation of causal treatment.